Isolasi dan Karakterisasi Kitosan dari Limbah Cangkang Kerang Asia (Corbicula fluminea): Isolation and Characterization of Kitosan from Asian Shell Waste (Corbicula fluminea) - Rizki Noor Amelia; Fika Aryati; Yurika Sastyarina (Proceeding of Mulawarman Pharmaceuticals Conferences, 2021)
Chitosan is a substance contained in shellfish that is the most biopolymer after cellulose. The study aims to determine the best yield of chitosan results of Asian shell isolation (Corbicula fluminea) based on variations in Sodium hydroxide concentration and length of deacetylation process, and to find the characteristics of chitosan isolation results based on International Standards. The process of chitosan isolation goes through several stages, namely deproteination using a solution of Sodium hydroxide 3,5% at a temperature of 65°C for 2 hours, demineralization using a solution of Hydrochloric acid 1N at a temperature of 65°C for 2 hours, and the stage of deacetylation that is optimized with variations in Sodium hydroxide concentration of 40%, 50%, and 60% and variations in the length of stirring time of 30, 60, and 90 minutes. The results showed the best chitosan yield of 90,1% obtained from the deacetylation process using a Sodium hydroxide concentration of 60% with a stirring time of 60 minutes. The resulting chitosan characteristics are white powder, odorless, soluble in 2% acetic acid, and has a water content of 0%.